Pembangunan Web Modul Prestasi Sebagai Alat Analisis Data Prestasi - Batubara, Supina (CV. Hawari, 2023)
Achievement is one of the critical aspects in the world of education that must be considered continuously. To improve the quality of education and make the right decision, a tool is needed that can analyze achievement data more efficiently. This study aims to develop an achievement web module that functions as a comprehensive achievement data analysis tool. The development of the achievement module web is carried out using a needs-based development approach and active participation from various related parties, such as teachers, lecturers, and administrative staff. This module is designed with an intuitive and responsive interface, allowing users to easily access and analyze performance data in real-time. The developed achievement module presents academic and non-academic achievement data visually in the form of graphs, tables and reports. Complete data analysis features allow users to identify achievement trends, patterns of increase or decrease in achievement, as well as factors that influence student or participant performance. The results showed that the achievement web module has increased the efficiency of achievement data analysis, provided more in-depth information, and supported more informed decision making. The use of this module has assisted related parties in formulating strategies and intervention programs aimed at improving overall performance.